Pengaruh Penyimpanan Jangka Panjang Berbasis Zeolit terhadap Kepadatan Spora dan Potensi Propagul Mikoriza pada Tanaman Sorgum - Istiqomah, Fatimah Nur; Novanto, Praditya Rizqi; Janati, Rahayu Ning (Universitas Gadjah Mada, 2025)
The research aimed to investigate the impact of storage duration (20 years versus less than one year) on the quantity of mycorrhizal spores and propagules within zeolite carrier media, using sorghum as the host plant. Spores were quantified through a sieving method and subsequent microscopic observation, while the numbers of propagules were determined through serial dilution down to 10-7. Following this, sorghum was cultivated, and root infection was evaluated. The findings indicated that mycorrhizae stored for less than one year yielded 416 spores/10 g and 620,000 propagules/g, compared to 259 spores/10 g and 170,000 propagules/g for those stored for twenty years. The identified spore types in both age groups included Acaulospora spp. 1, Acaulospora spp. 2, Glomus grape, and Glomus manihotis. This result suggested that the storage of mycorrhizae should be limited to less than one year to preserve a high number of spores and propagules.